PENGAWASAN DINAS PERIKANAN TERHADAP AKTIVITAS ILLEGAL FISHING KABUPATEN BANGGAI LAUT - BABO, JEKSON; ROMPAS, WELSON; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2017)
ABSTRACT : Speaking of Indonesian state marine products, who does not know, so many marine products are owned byIndonesia, and it is of more concern to the current government to manage, develop and safeguard against the perpetrators.Not a few cases that we can see in the mass media, many of which have been handled by the Ministry, such as illegal fishingconducted by foreign ships that do not have permission. Why the marine sector is very important because in it live thevarious living things that become the characteristic or icon of an area.Banggai Sea has one of the sea ions that become Icon of the Regency. The sea products in question are Cardinal Fish fishthat only exist in Banggai Laut. As a county icon it is appropriate that the fish be protected from the perpetrators of thecrime. This is a major responsibility of the Government, especially the Fisheries Department in conducting moresupervision.This study aims in addition to knowing the extent to which the supervision has been done, is to assist the relevant agencieshow to make supervision of illegal fishing can be effective.The research method used in this research is qualitative descriptive method and data collection technique throughobservation, interview, and document study. Based on the results of existing research that the task of supervision has nowbeen taken over by the Povinsi Fishery Department, now the task of the District Office is limited to Coordination, to try, bethe provincial authority.Keyword : monitoring, illegal fishing